The influence of service quality and corporate image of Royal Brunei Airlines: a partial least square approach - Chan, Tak-Jie; Irwan, Nurin Zahiah; Adzharuddin, Nor Azura; Huam, Hon Tat (Unimas Universiti Malaysia Sarawak, 2022)
The hospitality and tourism industries have become the pivotal industries that contribute to the growth of the nation's economy. However, fewer studies pay attention to the aviation industry where this industry has faced a lot of challenges and crises in the past decade. Hence, this study aims to examine the effects of service quality on the corporate image of Royal Brunei Airlines. The study utilized the SERVQUAL model to guide the study. A quantitative (survey) research design was employed using a total of 178 completed questionnaires obtained from the customers of Royal Brunei Airlines through purposive sampling. The data were then analyzed using Partial Least Squares Structural Equation Modelling through Smart-PLS 3.2.7. The results revealed that three (3) dimension of SERVQUAL (assurance, responsiveness, tangibles) has a positive and significant relationship with corporate image. However, empathy and reliability were found not significant to corporate image. Conclusion, implications, and suggestions for future study were also discussed.